1998
DOI: 10.1128/aem.64.3.1106-1114.1998
|View full text |Cite
|
Sign up to set email alerts
|

Methane and Trichloroethylene Degradation by Methylosinus trichosporium OB3b Expressing Particulate Methane Monooxygenase

Abstract: Whole-cell assays of methane and trichloroethylene (TCE) consumption have been performed on Methylosinus trichosporium OB3b expressing particulate methane monooxygenase (pMMO). From these assays it is apparent that varying the growth concentration of copper causes a change in the kinetics of methane and TCE degradation. For M. trichosporium OB3b, increasing the copper growth concentration from 2.5 to 20 μM caused the maximal degradation rate of methane (V max) to decrease from 300 to 82 nmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
92
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 40 publications
1
92
0
Order By: Relevance
“…In prior studies, Hylckama et al [36] used Methylosinus trichosporium OB3b to assess the transformation kinetics of chlorinated ethenes and obtained a k 1,TCE of <0.03 mL/(mg cells min) when Cu 2+ was omitted from the medium. Similarly, Lontoh et al [19] evaluated the cometabolic degradation of TCE using the same methanotroph and found that the k 1,TCE was 0.035 mL/(mg cells min) when expression of sMMO was repressed by adjusting the Cu 2+ concentration to 2.5 μM. Subsequently, Aziz et al [37] assessed the cometabolism of chlorinated solvents using a mutant methanotroph Methylosinus trichosporium OB3b PP358 and determined the k 1,TCE was 0.014 mL/(mg cells min).…”
Section: Effect Of Cu 2+ On Ch 4 Oxidation and Tce Degradationmentioning
confidence: 88%
See 2 more Smart Citations
“…In prior studies, Hylckama et al [36] used Methylosinus trichosporium OB3b to assess the transformation kinetics of chlorinated ethenes and obtained a k 1,TCE of <0.03 mL/(mg cells min) when Cu 2+ was omitted from the medium. Similarly, Lontoh et al [19] evaluated the cometabolic degradation of TCE using the same methanotroph and found that the k 1,TCE was 0.035 mL/(mg cells min) when expression of sMMO was repressed by adjusting the Cu 2+ concentration to 2.5 μM. Subsequently, Aziz et al [37] assessed the cometabolism of chlorinated solvents using a mutant methanotroph Methylosinus trichosporium OB3b PP358 and determined the k 1,TCE was 0.014 mL/(mg cells min).…”
Section: Effect Of Cu 2+ On Ch 4 Oxidation and Tce Degradationmentioning
confidence: 88%
“…Prior results suggest that a high copper-tobiomass ratio stimulates pMMO and represses sMMO expression in pure cultures [13,16,17]. Furthermore, Cu 2+ has been shown to alter pMMO expression up to 55-fold and to change its substrate affinity and specificity [18][19][20]. It has also been reported that sMMO activity is undetectable at a copper-tobiomass ratio of 45.64 mmol Cu·g −1 protein in the culture medium of Methylosinus trichosporium OB3b [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…f. Joergensen (1985). g. Lontoh and Semrau (1998); four measurements at different copper concentrations (2.5-20 mM). h. Calhoun and King (1997); values from eight root-associated methanotrophic isolates.…”
Section: Methane Oxidation Activity and Growth At Low Methane Mixing mentioning
confidence: 99%
“…The sMMO, an ironcontaining enzyme, is only expressed by a small number of methanotrophs and typically then only under conditions of copper deficiency (Dedysh et al, 2000;Dunfield et al, 2003;Semrau et al, 2010;Vorobev et al, 2011). Most extant methanotrophs, including those that have the ability to synthesize sMMO, also express pMMO, a copper containing enzyme, and such expression and activity increases with increasing copper availability (Lontoh and Semrau, 1998;Choi et al, 2003), i.e. there is a 'copperswitch' that regulates the expression of the two forms of MMO.…”
Section: Introductionmentioning
confidence: 99%